2011
DOI: 10.1007/s00432-011-1050-9
|View full text |Cite
|
Sign up to set email alerts
|

Solute carrier protein family may involve in radiation-induced radioresistance of non-small cell lung cancer

Abstract: The differentially expressed genes in both cell lines may contribute to their radioresistant phenotype. This extensive list of genes identified in the experiment provides a large body of potentially valuable information for studying the molecular mechanism(s) of radiosensitivity and identification of candidate molecular markers of radiation sensitivity. Thus, to our knowledge, the SLC gene superfamily is the first being reported to involve in acquired radioresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
0
24
1
Order By: Relevance
“…Deregulation of the amino acid transporter Slc7a7 is involved in multiple types of cancer, including gliobastoma, non-small cell lung cancer and multiple myeloma [60-62]. Studies conducted in recent years have demonstrated that diseases associated with Slc7a7 also include lysinuric protein intolerance and cystinuria [63].…”
Section: Discussionmentioning
confidence: 99%
“…Deregulation of the amino acid transporter Slc7a7 is involved in multiple types of cancer, including gliobastoma, non-small cell lung cancer and multiple myeloma [60-62]. Studies conducted in recent years have demonstrated that diseases associated with Slc7a7 also include lysinuric protein intolerance and cystinuria [63].…”
Section: Discussionmentioning
confidence: 99%
“…Data from another study also confirmed that SLC7A7 was upregulated at both mRNA and protein levels and that its overexpression was associated with poor prognosis in glioblastoma patients [28]. SLC7A7, involved in regulating amino acid transport, is closely linked to a variety of diseases [14][15][16][17]. A study focusing on ovarian cancers found that SLC7A7 may alter the influx/efflux of drugs from cells and thus modulate the chemotherapy response [16].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 58%
“…High expression of SLC7A7 is related to the prognosis of malignant glioma [14] and multiple myeloma [15] and drug resistance in ovarian cancer [16]. Moreover, the high expression of SLC7A7 is also associated with the radiotherapy sensitivity of lung cancer [17]. Barilli et al found an increase in the mRNA expression of the SLC7A7 gene in human monocytes during the differentiation process of macrophages [18].…”
Section: Ji Et Al: Function Of Slc7a7 In T-allmentioning
confidence: 99%
“…Some previous studies have shown that the abnormal gene expression regulation of SLC7A7 is associated with many malignant tumors. The up-regulated gene expression of SLC7A7 is associated with radiation-induced radioresistance in non-small cell lung cancer (Xie et al, 2011). Cheng et al (2010) indicated that the overall expression of SLC7A7 is related to chemoresistance in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%